EtOH-LN cryoembedding workflow to minimize freezing artifact in frozen tissues: A pilot study in preparing tissues compatible with mass spectrometry-based spatial proteomics application - Tan, Yong Chiang; Mustangin, Muaatamarulain; Rosli, Nurwahyuna; Wan Ahmad Kammal, Wan Syahira Ellani; Md Isa, Nurismah; Low, Teck Yew; Lee, Pey Yee; Chellappan, Dinesh Kumar; Jarmin, Razman; Zuhdi, Zamri; Azman, Azlanudin; Ian, Chik; et al. (Academic Press Inc., 2024)
Coolant-assisted liquid nitrogen (LN) flash freezing of frozen tissues has been widely adopted to preserve tissue morphology for histopathological annotations in mass spectrometry-based spatial proteomics techniques. However, existing coolants pose health risks upon inhalation and are expensive. To overcome this challenge, we present our pilot study by introducing the EtOH-LN workflow, which demonstrates the feasibility of using 95 % ethanol as a safer and easily accessible alternative to existing coolants for LN-based cryoembedding of frozen tissues. Our study reveals that both the EtOH-LN and LN-only cryoembedding workflows exhibit significantly reduced freezing artifacts compared to cryoembedding in cryostat (p < 0.005), while EtOH-LN (SD = 0.56) generates more consistent results compared to LN-only (SD = 1.29). We have modified a previously reported morphology restoration method to incorporate the EtOH-LN workflow, which successfully restored the tissue architecture from freezing artifacts (p < 0.05). Additional studies are required to validate the impact of the EtOH-LN workflow on the molecular profiles of tissues.